2021
DOI: 10.1042/etls20200354
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of model-membrane liposome-protein systems: complementarity of linear dichroism, circular dichroism, fluorescence and SERS

Abstract: A range of membrane models have been developed to study components of cellular systems. Lipid vesicles or liposomes are one such artificial membrane model which mimics many properties of the biological system: they are lipid bilayers composed of one or more lipids to which other molecules can associate. Liposomes are thus ideal to study the roles of cellular lipids and their interactions with other membrane components to understand a wide range of cellular processes including membrane disruption, membrane tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…To bridge this gap, a range of complementary methods that probe membrane proteins in environments that at least mimic a biological system are required. Flow linear dichroism (LD) 3–7 has been successfully used to determine the orientation of protein secondary structures with respect to the membrane normal of a range of liposomes 4,5,7–12 . However, scattering from the liposomes is larger than the LD signals and correcting for the scattering component at lower wavelengths is challenging 13 .…”
Section: Introductionmentioning
confidence: 99%
“…To bridge this gap, a range of complementary methods that probe membrane proteins in environments that at least mimic a biological system are required. Flow linear dichroism (LD) 3–7 has been successfully used to determine the orientation of protein secondary structures with respect to the membrane normal of a range of liposomes 4,5,7–12 . However, scattering from the liposomes is larger than the LD signals and correcting for the scattering component at lower wavelengths is challenging 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The author found that the signal from the lipid bilayer could be differentiated from the total liposome signal with protein with 1% and 10% concentration. As demonstrated before (Tukova et al, 2021), SERS analysis is sensitive in investigating liposome-protein systems. Here, the author presents a workflow to fully characterize nano-vesicles via SERS-tweezers, which paves the way towards label-free integrated extracellular vesicle analysis, which is important for cancer research.…”
Section: Monolayer Liposome Measurementsmentioning
confidence: 77%
“…Liposomes are small artificial vesicles made from amphiphilic lipids, such as PC and SM. They can be used as model systems 8 to study cell membrane dynamics in the laboratory. Several experimental techniques such as differential scanning calorimetry, 9 fluorescent imaging, 10 atomic force microscopy, and Raman imaging are used to study liposomes to understand the domain separation, domain co‐existence, lateral separation, and phase transition in biological membranes.…”
Section: Introductionmentioning
confidence: 99%